Measurement of the Total Lung Volume Using an Adjusted Single-Breath Helium Dilution Method in Patients With Obstructive Lung Disease - Liu, Qing; Zhou, Lingxiao; Feng, Peiling; Liu, Jinkai; Shen, Bin; Huang, Lili; Wang, Yingying; Zou, Yimin; Xia, Yang; Huang, Gang (Frontiers in Medicine, 2021)
Abstract Background Whole-body plethysmography (WBP) is the gold standard for measuring lung volume, but its clinical application is limited as it requires expensive equipment and is not simple to use. Studies have shown that the single-breath helium dilution (SBHD) method, which is commonly used in clinical practice, significantly underestimates lung volume in patients with obstructive lung disease (OLD). By comparing the differences in lung volume measured using SBHD and WBP, we aimed to establish a correction equation for the SBHD method to determine the total lung volume in patients with OLD of different severities. Methods From 628 patients with OLD simultaneously subjected to SBHD and WBP, 407 patients enrolled between January 2018 and November 2019 were in the training group and 221 enrolled between December 2019 and December 2020 were in the prospective verification cohort. The multiple linear regression equation was used for data in the training group to establish a correction equation for SBHD to determine the total lung volume, and this was validated in the prospective validation cohort. Results There was a moderate positive correlation between total lung capacity (TLC) determined using the SBHD (TLC (-SBHD)) and WBP methods (TLC (-WBP)) (r = 0.701; P < 0.05), and the differences between TLC (-SBHD) and TLC (-WBP) (△TLC) were related to the severity of obstruction. As the severity of obstruction increased, the TLC was underestimated by the SBHD method. We established the following correction equation: TLC (-adjusted SBHD)(L)=-0.669+0.756*TLC(-SBHD)(L)-0.047*FEV1/FVC+0.039*height(cm)-0.009*weight(kg) (r2 = 0.753 and adjusted r2 = 0.751). Next, we validated this equation in the validation cohort. With the correction equation, no statistical difference was observed between TLC (- adjusted SBHD) and TLC (-WBP) among the obstruction degree groups (P > 0.05). Conclusions The SBHD method is correlated with WBP to measure the total lung volume, but the SBHD method presents limitations in determining the total lung volume in patients with obstructive lung disease. Here, we established an effective and reliable correction equation in order to accurately assess the total lung volume of patients with OLD using the SBHD method.